2012
DOI: 10.4103/0970-9290.107415
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro comparison between the apical sealing abilities of resilon with Epiphany®sealer and gutta-percha with AH plus sealer

Abstract: Resilon (with Epiphany sealer) provided better radicular apical sealing in comparison to gutta percha (with AH Plus sealer).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Previous studies drew similar conclusions using leakage tests and found that Epiphany and Resilon were superior to gutta-percha (with AH Plus sealer). [ 19 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies drew similar conclusions using leakage tests and found that Epiphany and Resilon were superior to gutta-percha (with AH Plus sealer). [ 19 21 22 ]…”
Section: Discussionmentioning
confidence: 99%